THE MORPHOGENIC POTENTIAL OF SIBERIAN POTATO CULTIVARS IN TISSUE CULTURES - S. M. Ibragimova; A. V. Romanova; G. Kh. Myzgina; A. V. Kochetov (Вавиловский журнал генетики и селекции)
Potato is an important crop widely cultivated throughout the world. It is prone to several pathogenic fungi, viruses, and bacteria, which cause severe economic loss every year. Recent advances in plant  biotechnology have made it possible to produce resistant cultivars by plant genome editing. This approach allows crop modiications that would be diicult to obtain by conventional breeding techniques. A successful and reproducible plant system requires a responsive in vitro regeneration system. Three Siberian potato cultivars –Kemerovchanin, Tuleevsky, and Sapho – and two control cultivars – Golubizna and Nikulinsky – were chosen for in vitro response tests. The stem explants were excised from in vitro grown plantlets. Their stem explants were incubated on Murashige&Skoog (MS) medium supplemented with 1 mg/L transzeatin, 0.1 mg/L  IAA, and 10 mg/L GA3 with vitamins (medium P1). All the stages of cultivation up to obtaining fullledged regenerant plants were carried out on medium P1. Every two weeks the explants were transferred to fresh nutrient media. All cultivars formed calluses but difered  in terms of callus formation and in callus type. With further cultivation on the medium of the same composition, morphogenesis was observed: shoots formed on wound surfaces of the stem explants. Cultivars Tuleevsky, Kemerovchanin, and Golubizna showed high regeneration ability (73–97.7 %), while that of Sapho (63 %) was poor. All the Siberian cultivars were variable with regard to their morphogenic potentials. Root formation was observed in the shoots within 7 days on hormonefree MS. In the control (hormonefree medium), stem explants of all cultivars did not form calluses or develop shoots on the wound surfaces. The protocol described here is simple and eicient. It can be applied to other potato cultivars.